2019
DOI: 10.1136/bmjhci-2019-000017
|View full text |Cite
|
Sign up to set email alerts
|

Conformity of Diabetes Mobile apps with the Chronic Care Model

Abstract: BackgroundDespite the growing use of mobile applications (apps) for chronic disease management, the evidence on the effectiveness of this technology on clinical and behavioural outcomes of the patients is scant. Many studies highlight the importance of the theoretical foundations of mobile-based interventions. One of the most widely accepted models for the management of chronic diseases, such as diabetes, is the Chronic Care Model (CCM). In this study, we investigated the conformity of the selected diabetes mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Previous research showed promising results of eHealth interventions in terms of their effects on clinical outcomes and diabetes self-management [17]. Integrated, patientcentered care based on the CCM has been identified as very cost-effective for diabetes patients [18], but the conformity of mobile eHealth applications to the components of the CCM is generally weak [19]. Interventions appear to be most effective when an interactive format is used, such as text messaging [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research showed promising results of eHealth interventions in terms of their effects on clinical outcomes and diabetes self-management [17]. Integrated, patientcentered care based on the CCM has been identified as very cost-effective for diabetes patients [18], but the conformity of mobile eHealth applications to the components of the CCM is generally weak [19]. Interventions appear to be most effective when an interactive format is used, such as text messaging [20].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions appear to be most effective when an interactive format is used, such as text messaging [20]. Yet, many eHealth applications have just focused on some essential functionalities to monitor health parameters, such as tracking of blood pressure, blood glucose, weight, and activity [19,21]. There has been little focus on how both patients and providers can use patient-generated data together [22], and features enabling productive interactions between patients and staff are often lacking [23].…”
Section: Introductionmentioning
confidence: 99%